Impact of Missionary in Tribal Language - Abhishek Chhatar (Emerging Trends in Languages, 2025)
The introduction of Christian missionaries to the tribal areas of Asia, Africa, and Latin America had a deep influence on local languages, cultures, and identities. Although the promotion of Christianity is the first thing that comes to the mind when thinking of the work of missionaries, their language engagement has impacted literacy, education, and cultural preservation in many ways and for a long time. This study focuses on the first point, referring to the missionaries as the main supporters of the tribal languages by the language documentation, translation, and education, and on the second point, naming them as a reason for cultural decay because of the introduction of the dominant scripts, the alteration of oral traditions and the isolation of the native practices. The mixed-methods approach was used that combines historical analysis, ethnolinguistic literature, and case studies from India, Africa, and Latin America to trace how the missionary-led activities interfaced with language systems to result in hybrid identities. Information shows that although through Bible translations, grammar compilations as well as literacy programs missionaries brought about many tribal languages' standardization, these processes were mainly linked to religious conversion that caused a break in indigenous cosmologies. This research article reflects on the influence of missionary work in 3 aspects. writing down the oral languages which were not spoken of before; the missionary schools' involvement in the formation of the linguistic hierarchy; the outcomes of the tribal communities' socio-cultural changes resulting from linguistic shifts. In the end, the study presents arguments stating that the effects of the missionaries on tribal languages should not be seen as either preservation or destruction but rather as a complicated interplay of power, culture, and identity. This paper extends an interpretive lens for considering the ways in which the encounter of language affects cultural futures by locating missionary interventions both globally and locally.
Keywords: Christianity; indigenous cosmologies; missionaries; oral languages; tribal languages